Interventional behavioural change communication on HIV and aids related high risk behaviour among fishermen in Homabay and Siaya Counties, Kenya - Akobi, William Kala; Oyore, John Paul; Otieno, George Ochieng (International Journal Of Community Medicine And Public Health, 2022)
Background: Risky sexual behaviors such as sexual concurrency, sexual networks (fish for sex exchange) and unprotected sex, have been reported as the main cause of STIs/HIV infections among the fisher folks. Behavioural change mechanisms such as condom use, and abstinence are some of the interventions used in the prevention HIV/AIDS spread in Kenya. Methods: This was a follow up study on a three tie quasi-experimental study involving 246 randomly selected fisher folks in Mbita and Usenge along Lake Victoria. The study had three phases. baseline, intervention and endline. The survey used questionnaires to collect data among respondents. Using a sample frame in the beach management unit offices, fisherfolks were identified and invited to participate. Consent was obtained from participants Results: Various variables were influenced by behavior change communication strategies used. These includes use of condom every time of sexual encounter p>0.000, risk associated with non-condom use p>0.004, stopping using condom and fear of getting HIV/AIDS p>0.009, Sexual intercourse without condom use is dangerous p>0.000, whether remembering to use condom every time of sex is difficult P.0.000, whether they are keeping many sexual partners p=0.004, receiving fish/money in exchange for sex in last six months p=0.006. Conclusions: Multiple sexual partners, non-condom use, fish for sex, alcohol consumption and circumcision were significantly associated with risky sexual behavior among the Fisherfolks, therefore other existing interventions need to be intensified to supplement behavior change communication to curb sexually transmitted diseases and further spread of HIV and AIDS.